The identification of a novel antibody for CD133 using human antibody phage display. Issue 13 (22nd May 2018) - Glumac, Paige M.; Forster, Colleen L.; Zhou, Hong; Murugan, Paari; Gupta, Shilpa; LeBeau, Aaron M.
Abstract : Background: The transmembrane glycoprotein CD133 is believed to be a marker of adult prostate stem cells and cancer stem/initiating cells. Investigating the role of CD133 in the normal biology of the prostate and in cancer is complicated by the lack of a sensitive and accurate antibody for its detection. Here, we describe the characterization of a unique antibody identified using human antibody phage display that can recognize CD133 in both formalin‐fixed tissues and cell lines. Methods: A human single‐chain variable fragment (scFv) antibody phage display library possessing a diversity of 8 × 10 9 was screened against fully glycosylated recombinant CD133. A counter screen was performed against deglycosylated CD133 to select for clones that preferentially recognized a glycosylation‐independent epitope. The lead scFv was analyzed by flow cytometry and cloned into a rabbit immunoglobulin scaffold for immunohistochemistry (IHC). Results: The antibody designated HA10 was found to bind a glycosylation‐independent epitope on the peptide backbone of CD133 with high affinity. As a reagent for flow cytometry, HA10 detected CD133 more accurately than a commonly used commercially available antibody. IHC analysis with HA10 documented the staining of basal cells and luminal cells in healthy prostate sections. Weak staining of luminal cells was observed in adenocarcinoma sections at a very low frequency. Examination of a LuCaP patient‐derived xenograft tissue microarray found that only three of the LuCaP models were positive for CD133. The three CD133 pos LuCaP models all originated from non‐AR driven metastatic prostate cancer with neuroendocrine differentiation. Subsequent interrogation of liver biopsies from a patient who failed second‐generation anti‐androgen therapy found high levels of CD133 staining. The original transurethral resection of the prostate from that patient was, however, absent of CD133. Conclusions: We have developed a novel antibody that was able to detect CD133 by both IHC and flow cytometry. Using HA10 as an IHC reagent, we found that CD133 is a marker for a very rare cell type in both healthy prostate and adenocarcinoma sections. Our preliminary investigation also suggests that there may be an association between CD133 and non‐AR driven prostate cancer with neuroendocrine differentiation.